Influence of Health Education on the Negative Impact of Smoking on Increasing Student Knowledge at SD Inpres Peo - Arranury, Zil Fadhilah; Ansyar, Dian Ihwana; Lagu, Abd. Majid HR.; Nuhairah, Alisya; Rezki, Nur Afifah (Unihealth Community Research, 2026)
Exposure of school-age children to information and environmental influences that may encourage smoking behavior remains a critical concern, particularlybecause their understanding of the dangers of smoking is generally still limited.  This article presents the results of a study aimed at measuring the effect ofcounseling on the dangers of smoking on the knowledge of students at SD Inpres Peo. The research employed a quantitative method using a one-group pre-experimental design, specifically the One-Group Pre-Test and Post- Test model. The study population consisted of all fourth-, fifth-, and sixth-gradestudents at SD Inpres Peo, with a total sample of 62 students. The findings indicate a significant improvement in students’ knowledge after the counseling intervention. During the pre-test, most students demonstrated a low level of knowledge (58%), whereas after the intervention, the majority showed anadequate level of knowledge (67.8%). Results from the Paired Sample T-Test revealed that the mean knowledge score increased from 7.97 to 9.11 following the intervention (p = 0.000). The educational program on the dangers of smoking had a positive impact on increasing students’ knowledge, particularly among fifth-grade students. Support from teachers and the school principal plays an essential role in ensuring the sustainability of the program through thematic learning activities and other school initiatives. The program is expected to foster early behavioral protection and strengthen social norms within the schoolenvironment. Despite these positive outcomes, several challenges remain, including student motivation, program sustainability, and the need for long-term evaluation to ensure behavioral change. The expected outcomes of the program extend beyond improved knowledge scores, encompassing the development of collective awareness and the reinforcement of preventive values.